Pengaruh Pendekatan Pembelajaran Berbasis TPACK Terhadap Hasil Belajar Siswa Kelas V Pada Mata Pelajaran IPAS Di SDN 17/I Rantau Puri - Saputra, Irgiano Sulistiawan Purnama; Yantoro, Yantoro; Sholeh, Muhammad (Universitas Muhammadiyah Magelang, 2024)
This study aims to determine the effect of the TPACK-based learning approach on student learning outcomes in elementary schools. This research was conducted at SDN 17/I Rantau Puri in the 2023/2024 school year. The type of pre-experimental research (pre-experiment) with a pre-test post-test one group design research design, namely the research only used one experimental class, and no other class was used as a control class. Data collection techniques were obtained by giving tests to students before and after treatment. The test was carried out by providing instruments in the form of questions on the subject of science. Then, the data was processed to compare learning outcomes between before and after treatment. The results of the study obtained, based on the results of the t-test using SPSS 20 with the paired sample t-test, obtained a calculated t value greater than the t table, namely 9.109> 2.055. So Ho is rejected and Ha is accepted. The conclusion obtained through this study is that there is a significant influence of the TPACK-based learning approach on student learning outcomes.